Cash Waqf Linked Sukuk (CWLS) As a Strengthener of the Cash Waqf Ecosystem in Indonesia - Kamaluddin, Imam; Okta Safitri, Dara Ayu; Risnan Putri, Eka (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by waqf problems related to the potential and management of waqf that have not been maximized. Then the government seeks to develop waqf by bringing up new instruments that serve as state infrastructure financing. Law 41 of 2004 relating to waqf is supported by Indonesian ulemas. Cash waqf is a flexible instrument that the public can easily reach, so it has great potential to strengthen the waqf ecosystem. And the government's efforts to increase the potential for cash waqf are planning cash waqf-linked sukuk instruments, namely waqf-based sukuk investments. This study aims to identify and analyze the CWLS program management system that can strengthen the cash waqf ecosystem. This study uses a descriptive qualitative method with a literature review approach, and the researcher uses the technical triangulation method. The results of this study indicate that cash waqf linked sukuk can strengthen the cash waqf ecosystem. So that cash waqf can contribute to improving financial instruments and community social investment. And can facilitate money endowments, both temporary and permanent. To place cash waqf in social investment instruments that are safe, productive, and have a big impact on society.